SHELVING DI PERPUSTAKAAN SD N 8 BETUNG KABUPATEN BANYUASIN - Nusantara, M. Satrio; Syutaridho, Syutaridho (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The library in this very advanced era can be said to be a place in which there is a myriad of information Libraries are divided into several types, namely school libraries, public libraries. special library. and the college library. Each has specific characteristics. The functions and purposes of each according to the needs of its users. For example, Library will be more oriented to the needs of its students. A library should have its own purpose and systems tailored to the needs to maximize its functionality. The system in question can be in the form of a processing system, book arrangement system (selving), room arrangement system and so on. Terminological selving means Stacking books on shelves, movement. Stacking system on shelves, cabinets with certain regulations. With this dredging, it can be immediately known exactly the location of the collection. Therefore, Shelving is very influential on the library materials library so that students have an understanding the collecti on search process. Because the arrangement is sequential and cistere ntial, if arranged with the right system, it will greatly facilitate litera ture in tracing the Shelving collection is the final stage in processing library materials.